Stress and Coping in a Self-Isolated Family during COVID-19 Pandemic - Kryukova, T.L.; Ekimchik, O.A.; Opekina, T.P.; Shipova, N. (Socialʹnaâ Psihologiâ i Obŝestvo, 2020)
Objective. To find out the level of stressfulness of inside family isolation in Russia; coping with the negative effects of a pandemic, fear and isolation. Background. The situation of a health threat causes unexpected stress enhancing the fear of getting infected, uncertainty, anxiety. The coronavirus disease outbreak has introduced special demands: to lockdown not to get infected. But it also “triggers” adaptive coping behavior. It`s suggested that situation-adequate coping, as well as close relationships based on support, reduce the effects of coronavirus threat. Domestic violence and its effects (physical abuse, mental illness, PTSD) negatively affect family relationships, maybe as deadly as the coronavirus, require immediate prevention. Study design. A mini-longitudinal empirical study was conducted online at the beginning (27.03.2020—12.04.2020) (N1=248) and in the second half of lockdown (28.04.2020—03.05.2020) (N2=310). The role of stressors in changing family relationships has been correlated with the impact of catching COVID-19 threat and self-isolation on the psychological state of family members. Participants. 558 volunteers aged 18—87, including 425 women and 117 men; the majority of them (66%) have their own family — 369 are married/in a relationship; work. Measurements. A questionnaire created by the authors on the basis of international projects assessing impact of stress and self-isolation on family relationships, standardized anxiety and depression scales; coping scales. Results. Negative outcomes of the threat of infection and isolation are reduced if coping is adequate, emotional support from family members, and their views on the necessary daily changes are consistent. Stress levels are higher in single people. Having a partner is important for ways of coping choice. Conclusions. Stress generating from the threat of catching virus/COVID-19 experienced by people during lockdown in close/family relationships is normative as long as they use coping strategies, adequate to the situation (acceptance, positive reappraisal) with a low frequency of choosing less adequate strategies. Цель. Определение стрессогенности ситуации изоляции, переживаемой россиянами в семье; способов совладания с негативными последствиями пандемии, страха и изоляции. Контекст и актуальность. Неожиданный стресс, связанный со вспышкой коронавирусной инфекции (COVID-19), предъявляет особые требования (изолирование дома) и актуализирует страх заражения, неопределенность и тревожность. Он же «запускает» адаптивное совладающее поведение, усилия приспособиться, бороться. Сделано предположение, что адекватный ситуации копинг, поддерживаемый семьей и близкими отношениями, основанными на поддержке, снижает стресс, вызванный угрозой заражения. Домашнее насилие и его эффекты (включая физическое насилие, психические заболевания, посттравматическое стрессовое расстройство) негативно влияют на семейные отношения, могут быть столь же смертельными, как и коронавирус, требуют немедленной профилактики. Дизайн исследования. Мини-лонгитюдное эмпирическое исследование проведено онлайн в начале (27.03.2020—12.04.2020) (N1=248) и во второй половине периода самоизоляции (28.04.2020—03.05.2020) (N2=310). Роль стрессоров в изменении внутрисемейных отношений соотнесена с влиянием стресса, вызванного угрозой заражения COVID-19 и самоизоляции на психологическое состояние членов семьи. Участники. 558 добровольных участников в возрасте 18—87 лет, из них 427 женщин и 131 мужчина; большинство (66%) имеют собственную семью — 369 человек состоят в браке/в отношениях; работают. Методы (инструменты). Созданный авторами на основе международных проектов опросник о влиянии стресса и самоизоляции на семейные отношения, стандартизированные шкалы тревоги и депрессии; копинг-шкалы. Результаты. Существующие негативные последствия угрозы заражения и изоляции снижаются в случае адекватности копинга, эмоциональной поддержки от членов семьи, согласованности их взглядов на необходимые повседневные изменения. Уровень стресса выше у одиноких людей. Наличие партнера имеет значение для выбора способа совладания. Основные выводы. Стресс, вызванный угрозой зараженияCOVID-19, переживаемый людьми при самоизоляции в близких/семейных отношениях, является нормативным при условии использования ими адекватных ситуации копинг-стратегий (принятие, позитивная переоценка) при невысокой частоте обращения к менее адекватным стратегиям.